Load balancing based on nodes distribution in mobile sensor network - Kartinah, Zen; Halikul, Lenando; Mohamad Nazim, Jambli (IEEE, 2011)
In a large scale mobile sensor network, some coordinators may exhaust energy earlier if they are connected with excessive number of mobile nodes compared to the others. Balancing the load could stable and prolong the network lifetime, maximizes coordinators capabilities and improves net-work performance. In this paper, a mechanism to balance the coordinators' load based on the distribution of mobile sensor nodes in IEEE 802.15.4 protocol is presented. In this scheme, a coordinator is a static cluster head that collects data from the associated mobile sensor nodes. From the simulation results, the load balancing scheme successfully balances the distribution of mobile sensor nodes that attached to each coordinators. This therefore balances the energy consume among the coordinators and indirectly, delay in data reception is reduced when there are large number of mobile nodes in the system.